Thoracoscopic repair of esophageal atresia with tracheoesophageal fistula: Basics of technique and its nuances - Ravi Prakash Kanojia; Neerja Bhardwaj; Deepak Dwivedi; Raj Kumar; Saajan Joshi; Ram Samujh; K. L. N. Rao (Wolters Kluwer Medknow Publications, 2016)
Aim: To review the technique of thoracoscopic repair of esophageal atresia with tracheoesophageal fistula (TREAT) and results reported in literature and with authors' experience. Patients and Methods: The technique of TREAT was reviewed in detail with evaluation in patients treated at authors' institution. The patients were selected based on selection criteria and were followed postoperatively. The results available in literature were also reviewed. Results: A total of 29 patients (8 females) were operated by TREAT. Mean age was 2.8 days (range 2-6 days). Mean weight was 2.6 kg (range 1.8-3.2 kg). There was a leak in four patients, and two patients had to be diverted. They are now awaiting definitive repair. Twenty-one patients have completed a mean follow-up of 1.5 years and are doing well except for two patients who had a stricture and underwent serial esophageal dilatations. The results from current literature are provided in tabulated form. Conclusions: TREAT is now a well-established procedure and currently is the preferred approach wherever feasible. The avoidance of thoracotomy is a major advantage to the newborn and is proven to benefit the recovery in the postoperative patient. The technique demonstrated, and the tweaks reported make the procedure easy and is helpful to beginners. The outcome is very much comparable to the open repair as proven by various series. Various parameters like leak rate, anastomotic stricture are the same. The outcome is comparable if you TREAT these babies well.